Nrf2-dependent effects of CDDO-Me on bactericidal activity in macrophage infection models - Deramaudt, Therese B.; Chehaitly, Ahmad; Bonay, Marcel (Frontiers in Immunology, 2025)
IntroductionDiabetes and chronic kidney disease (CKD) increase susceptibility to bacterial infections, particularly Staphylococcus aureus, which is associated with highmortality in CKD patients. Dysregulated macrophage activity and excessive oxidative stress exacerbate immune dysfunction and inflammation in these conditions. Nrf2 (nuclear factor erythroid 2–related factor 2) is a key regulator of antioxidant defenses and macrophage function. CDDO-Me, a synthetic triterpenoid, activates Nrf2, providing antioxidant and anti-inflammatoryeffects. However, its precise role in modulating macrophage activity, polarization, and bacterial clearance remains unclear.MethodsThe effects of CDDO-Me on macrophage function were evaluated in vitro (THP-1 and RAW 264.7 macrophages) and an in vivo Nrf2 knockout mouse model. Nrf2 activation was assessed via Western blot and luciferase reporter assays, oxidative stress was measured using CellROX reagent, and inflammatory responses were quantified by RT-qPCR. Intracellular S. aureus survival and macrophage polarization markers were analyzed to investigate the role of CDDO-Me in enhancing bactericidal activity.ResultsOur results showed that CDDO-Me activated the Nrf2 signaling pathway, reducing oxidative stress and inflammation in macrophages by downregulating pro-inflammatory cytokines (IL-1β, TNF-α). It modulated macrophage polarization, decreasing M1 and M2 marker expression, and significantly enhanced bactericidal activity against S. aureus. These effects were Nrf2-dependent, as demonstrated in knockout models.ConclusionThe ability of CDDO-Me to regulate oxidative stress, inflammation, and bacterial clearance underscores its therapeutic potential for managing inflammatory and infectious diseases indiabetes and CKD.